2021
DOI: 10.3389/fimmu.2021.696536
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Single Cell RNA-seq Analysis of Non-Myeloid Circulating Cells in Late Sepsis

Abstract: BackgroundWith the successful implementation of the Surviving Sepsis Campaign guidelines, post-sepsis in-hospital mortality to sepsis continues to decrease. Those who acutely survive surgical sepsis will either rapidly recover or develop a chronic critical illness (CCI). CCI is associated with adverse long-term outcomes and 1-year mortality. Although the pathobiology of CCI remains undefined, emerging evidence suggests a post-sepsis state of pathologic myeloid activation, inducing suboptimal lymphopoiesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…It has been reported that mice deficient for either IFNAR1 or IFNβ generate significantly less mature monocytes with reduced expression of ISG 29,30 , suggesting a potential causal link between diminished IFN-I response and impaired myelopoiesis. In accordance, we observed a similar significant loss of non-classical monocytes in late-stage sepsis patients 21 , further substantiating the clinical relevance of the LPS-SI model to other SI-related pathophysiological conditions such as sepsis. Most importantly, our functional experiments revealed that IFNβ reverses the immunosuppressed state of LPS-treated monocytes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…It has been reported that mice deficient for either IFNAR1 or IFNβ generate significantly less mature monocytes with reduced expression of ISG 29,30 , suggesting a potential causal link between diminished IFN-I response and impaired myelopoiesis. In accordance, we observed a similar significant loss of non-classical monocytes in late-stage sepsis patients 21 , further substantiating the clinical relevance of the LPS-SI model to other SI-related pathophysiological conditions such as sepsis. Most importantly, our functional experiments revealed that IFNβ reverses the immunosuppressed state of LPS-treated monocytes.…”
Section: Discussionsupporting
confidence: 84%
“…f , IFN-I activity over the inferred monocyte differentiation trajectory from HSCs to non-classical monocytes, colored based on time point. g , UMAP of blood monocytes from a late (>14 days) sepsis patient cohort (left panel 21 ), along with cell density calculated for each health status (healthy volunteer or sepsis patient, right panel). h , log2(relative abundance) of cell types compared between late sepsis patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S3E-G). 28,29 Co-expression of inhibitory receptors can substantially impair T lymphocyte function, such as the production of IL2, IL4, and TNF (Fig. 3I), and induce a reduction in cell number (Fig.…”
Section: S9f)mentioning
confidence: 99%